ENTREPRENEURSHIP EDUCATION AND ENGINEERING STUDENTS’ ENTREPRENEURIAL INTENTIONS: THE MEDIATING ROLES OF ENTREPRENEURIAL SELF-EFFICACY AND ATTITUDE (NAU Journal of Technology and Vocational Education, 2025)
Drawing on insights from the theory of planned behaviour and social cognitive career theory, this study empirically examines the serial mediating effect of entrepreneurial self-efficacy (ESE) and entrepreneurial attitude on the relationship between entrepreneurship education (EE) and entrepreneurial intentions (EIs). This study adopted a quantitative approach and survey research design. Data were collected from 248 engineering students in the Federal Polytechnic, Idah, Kogi State, Nigeria, using a self-reported questionnaire. The study performed serial mediation analysis using the Hayes-PROCESS Macro. Findings show that EE enhances students' ESE, entrepreneurial attitude and EIs. Results also indicate that ESE and entrepreneurial attitude individually and sequentially mediate the association between EE and EIs. The study concludes that ESE and entrepreneurial attitude are mechanisms through which EE positively affects EIs. The results have implications for EE curriculum developers.